The effect of SMS reminders on health screening uptake: A randomized experiment in Indonesia - Marcus, Maja E.; Reuter, Anna; Rogge, Lisa; Vollmer, Sebastian (Journal of Economic Behavior & Organization, 2024)
As cardiovascular diseases (CVD) become the leading cause of death in low- and middle-income countries (LMICs), this raises new challenges for health systems. Regular screening is a key measure to manage CVD risk, but the uptake of such services remains low. We conducted a randomized controlled trial in Indonesia to assess whether personalized and targeted text messages increase the usage of public screening services for diabetes and hypertension in the at-risk population. Our intervention increased screening uptake by 6.6 percentage points. We show that text messages can be effective in the context of a relatively new disease burden in LMICs, where population responses may still be shaped by low salience and missing screening routines.
CRIS-Team Scopus Importer:2024-09-20
Keywords: Health; Health systems; Information; mHealth; Noncommunicable diseases; Screening uptake; Text message reminder